Penggunaan Accelerometer dan Strain Gauge Sebagai Sensor Untuk Mendeteksi Kerusakan Pahat Potong - Nanda Aulia; Muhammad Rizal; Amir Zaki Mubarak (Jurnal Teknik Mesin Unsyiah, 2019)
The damage of cutting effect the product a lot, thus reducing the quality and dimensional change of the product. This research aims to monitor damage of cutting tool throught the accelerometer and strain gauge sensors on the process of turning Rod hydraulic cylinder SAE 1045 using cutting carbide coated. The machining process is carried out by the variation of cutting parameters, depth of cut 0,5 and 1,0, feed rate o,5 and 0,7 mm/min, and constant cutting speed of 1300 rpm. This experiment is conducted on three cutting tool condition they are new, medium wearing (0,15 mm) and critical wearing (0,3 mm). The censors used are accelerometer and strain gauge which are placed in the holder. The result show that kurtosis, RMS and standard deviation parameters are influenced by the tooling condition. Have the relation toward the wearing change of tooling, this case is showed by the existence of progress from the new, medium and critical tooling test. As for amplitude strain gauge signal also showed a significant change when there is damage to the wearing tools. This showed that the bigger wearing happening the higher signal out going.